The experiences of peer relationships amongst autistic adolescents: A systematic review of the qualitative evidence - Cresswell, Lily; Hinch, Rebecca; Cage, Eilidh (Research in autism spectrum disorders, 2019)
•Autistic adolescents understand the concept of friendship and tend to want to have friends.•Due to difficulties with social communication, forming and maintaining friendships can be challenging, with multiple barriers.•Feelings of loneliness and social isolation can result from difficulties with making friends and from peer victimisation, which can lead to mental health problems.•Further work is needed to make social skills support or training available to all autistic adolescents who desire it. Peer relationships can be especially difficult for autistic adolescents, given their marked social communication difficulties. The purpose of this systematic review is to synthesise reported qualitative findings on how autistic adolescents experience peer relationships, including the rewards and challenges, from their perspective. The review includes the perspectives of others (e.g. parents, support workers), from included papers where these were reported in addition to the adolescent viewpoint. PRISMA guidelines and the Joanna Briggs Institute meta-aggregative approach to qualitative synthesis informed this review process. Articles included were published in the last ten years, specific to autistic adolescents between the ages of 10 and 19. Of the 75 articles meeting eligibility for full-text review, ten matched the final inclusion criteria. Findings relating to four main themes emerged from the qualitative synthesis: understanding friendship, having and wanting friends, challenges of peer relationships and overcoming challenges. Fourteen sub-topics are described in detail, for example, that autistic adolescents do have and want friends, though this is often not easily achieved, leading to feelings of loneliness. Findings also revealed experiences of peer rejection and victimisation, and specific factors that might make building positive peer relationships difficult, such as group settings. Autistic adolescents face a number of difficulties with understanding social rules and conventions, which seem to make peer relationships difficult. However, due to many autistic adolescents having a desire for friendship, some have developed ways of overcoming these challenges. This review highlights that additional support is needed to support the development of autistic adolescents’ social skills and awareness; further research is needed to establish how this could be done most effectively.